Damping low frequency oscillations in power systems using iteration particle swarm optimizations - Usman, Jafaru (2012)
The major concern in power systems has been the problem of low frequency oscillations (LFO) that results in the reduction of the power transfer capabilities. The applications of power system stabilizers (PSS) are commonly employed to dampen these low frequency oscillations. The parameters of the PSS are tuned by considering the Heffron-Phillips model of a single machine infinite bus system (SMIB). Tuning of these parameters for the system considered can be done using iteration particle swarm optimization (IPSO) technique in this paper; mainly the lead lag type of PSS was used to damp these low frequency oscillations. The proposed technique (IPSO)'s capabilities are compared with the traditional PSO and genetic algorithm (GA) technique in terms of parameter accuracy and computational time. Also the results of nonlinear simulations and eigenvalue analysis reveals that, the IPSO is much better optimization technique as compared to traditional PSO and GA.